IMPLEMENTASI GAYA KEPEMIMPINAN LAISSEZ-FAIRE KEPALA SEKOLAH TERHADAP PENINGKATAN PRESTASI NON-AKADEMIK DI SEKOLAH DASAR - Jannah, Raudhatul; Suriansyah, Ahmad; Budi Harsono, Arta Mulya (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The implementation of Laissez-Faire leadership style by the principal that is carried out appropriately and wisely will have a big impact on improving students' non-academic achievements in elementary schools. This study aims to explore the implementation of Laissez-Faire leadership style of the principal of SDN Alalak Utara 2 in improving students' non-academic achievements in schools. This study uses a qualitative approach with a causative study design. The research sample includes the principal, teachers, coaches, and students. The results of the analysis explain that the use of a free-based leadership style can improve students' non-academic achievements, this is proven by interview data, observations and documentation found by researchers at SDN Alalak Utara 2. This research activity was conducted to prove that a free leadership style can also have a positive impact on schools, especially on the achievements achieved by schools.